Differences in simulated doctor and patient medical decision making: a construal level perspective. - Jiaxi Peng (Public Library of Science (PLoS), 2013)
Background Patients are often confronted with diverse medical decisions. Often lacking relevant medical knowledge, patients fail to independently make medical decisions and instead generally rely on the advice of doctors. Objective This study investigated the characteristics of and differences in doctor-patient medical decision making on the basis of construal level theory. Methods A total of 420 undergraduates majoring in clinical medicine were randomly assigned to six groups. Their decisions to opt for radiotherapy and surgery were investigated, with the choices described in a positive/neutral/negative frame × decision making for self/others. Results Compared with participants giving medical advice to patients, participants deciding for themselves were more likely to select radiotherapy (F1, 404 = 13.92, p = 011). Participants from positive or neutral frames exhibited a higher tendency to choose surgery than did those from negative frames (F2, 404 = 22.53, p<.001). The effect of framing on independent decision making was nonsignificant (F2, 404 = 1.07, p = 35); however the effect of framing on the provision of advice to patients was significant (F2, 404 = 12.95, p<.001). The effect of construal level was significant in the positive frame (F1, 404 = 8.06, p = 005) and marginally significant in the neutral frame (F2, 404 = 3.31, p = 07) but nonsignificant in the negative frame (F2, 404 = .29, p = 59). Conclusion Both social distance and framing depiction significantly affected medical decision making and exhibited a significant interaction. Differences in medical decision making between doctors and patients need further investigation.